Das Erhabene im phänomenologischen Sinne: Die affektiv leibliche Erfahrung des Raumes - Breuer, Irene (Labyrinth, 2020)
The Sublime in a phenomenological sense: The Affective Bodily Experience of Space The aim of the following paper is to redefine the sublime in phenomenological terms, a task long overdue. Departing from Kant, it claims that the phenomenological sublime is an emotion aroused neither by the power of our reason transcending the inadequacy of imagination as it concerns nature, nor by the overwhelming powers of imagination as it concerns an artwork, but by the excess of sensuousness over conceptuality, which is bodily felt. This shift into bodily apprehensions, though advanced by empirical psychologists, took place in the twentieth century resulting from Husserl's and Merleau-Ponty's reformulation of the affective sphere of the body and of its concomitant experience of space. Their criticism of compossibility and harmony lead to a disruption of the bodily metaphoric order inherent to artistic representation. This becomes evident in the conception of present architecture, as the works of Tschumi and Eisenman show. The phenomenological emotion of sublimity expresses thus the affective bodily experience of space.